Effect of lipopolysaccharide (LPS) and peptidoglycan (PGN) on human mast cell numbers, cytokine production, and protease composition - Wu Yalin; Kulka Marianna; Swindle Emily; Kirshenbaum Arnold S; Metcalfe Dean D (BMC Immunology, 2008)
Abstract Background Human mast cell (HuMC) maturation occurs in tissues interfacing with the external environment, exposing both mast cell progenitors and mature mast cells, to bacteria and their products. It is unknown, however, whether long- or short-term exposure to bacteria-derived toll-like receptor (TLR) ligands, such as lipopolysaccharide (LPS) or peptidoglycan (PGN), influences HuMC biology. Results Over 6 wks of culture, LPS had minimal effect on HuMC numbers but increased CD117, tryptase and chymase expression. PGN inhibited HuMC development. For mature mast cells, LPS in the presence of rhSCF (10 ng/ml) increased CD117, tryptase, chymase and carboxypeptidase expression, primarily in CD117low HuMC. LPS decreased FcεRI expression and β-hexosaminidase release; but had no effect on LTC4 and PGD2 production. PGN reduced HuMC numbers; and CD117 and tryptase expression. IL-1β and IL-6 (in addition to IL-8 and IL-12) were detected in short-term culture supernatants of LPS treated cells, and reproduced the increases in CD117, tryptase, chymase, and carboxypeptidase expression observed in the presence of LPS. Comparative studies with mouse bone marrow-derived mast cells from wild type, but not TLR4 knockout mice, showed increases in mRNA of mouse mast cell chymases MMCP-1, MMCP-2 and MMCP-4. Conclusion PGN inhibits HuMC growth, while LPS exerts its primary effects on mature HuMC by altering cytokine production and protease composition, particularly at low concentrations of SCF. These data demonstrate the ability of bacterial products to alter HuMC mediator production, granular content, and number which may be particularly relevant at mucosal sites where HuMC are exposed to these products.